1997
DOI: 10.1016/s0035-9203(97)90087-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of periportal fibrosis in schistosomiasis mansoni in Brazil

Abstract: In patients with hepatosplenic schistosomiasis, characteristic thickening of the walls of the portal vein in the hilus and its central and peripheral branches is observed. In an area of high prevalence of the disease in Brazil, 424 individuals older than 5 years have been examined by abdominal ultrasonography and 146 presented fibrosis, classified as central in 31 (21%), peripheral in 56 (38%), and both central and peripheral in 59 (40%). The mean ages of the subjects in the 3 groups were 45.7, 24.1 and 31.9 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 11 publications
2
14
0
3
Order By: Relevance
“…endoscopic and sonographic findings and variceal bleeding were compared had conflicting results: whereas in earlier studies a relationship between the sonographic grade of periportal fibrosis, the occurrence of variceal haemorrhage prior to examination and/or the grade of oesophageal varices had not been found (Homeida et al 1988;Davidson et al 1991), more recent investigations showed that the sonographic grade of periportal fibrosis is related to prior variceal haemorrhage (Richter et al 1992a;Domingues et al 1993;Abdel-Wahab et al 1993;Eltoum et al 1994;Gerspacher-Lara et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…endoscopic and sonographic findings and variceal bleeding were compared had conflicting results: whereas in earlier studies a relationship between the sonographic grade of periportal fibrosis, the occurrence of variceal haemorrhage prior to examination and/or the grade of oesophageal varices had not been found (Homeida et al 1988;Davidson et al 1991), more recent investigations showed that the sonographic grade of periportal fibrosis is related to prior variceal haemorrhage (Richter et al 1992a;Domingues et al 1993;Abdel-Wahab et al 1993;Eltoum et al 1994;Gerspacher-Lara et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral fibrosis was considered to be present when three peripheral portal branches with thickened walls (> 2 mm) were described; thickening of the gallbladder wall (> 5 mm) was also considered (Gerspacher-Lara et al 1997). The presence of portosystemic collaterals were annotated (Domingues et al 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Key words: schistosomiasis -ultrasound -physical examination -spleen -liver -portal hypertension Ultrasound (US) has been routinely used in the evaluation of hepatosplenic schistosomiasis mansoni for the last 20 years (Pinto-Silva et al 1994, Lambertucci et al 1996, Gesparcher-Lara et al 1997, Martins et al 1998. The use of US is justified by its low cost, and portability which made it possible to be used in field-based studies.…”
Section: The Best Way To Appraise the Size Of Abdominal Organs Remainmentioning
confidence: 99%